Evaluation on Management of Pesticide Poisoning of Hospitalized Patients in Hospital A Yogyakarta during thePeriod of January 2001 until December 2002 - Nurlaila .; Imono Argo Donatus; Meiyanto Edy (Indonesian Journal of Pharmacy, 2005)
The study on pesticide poisoning management was performed in Hospital A, Yogyakarta during the period of January 2001 until December 2002. This is designed to investigate wether the implementation of the poison management has already been conducted properly and to assess the percentage of the succesful therapy in the hospital. The present study was conducted using a descriptive observational design which include the case series reports by a retrospective method. The subject were 34 pesticide poisoning-hospitalized patients. Data were collected based on patient medical records such as the number of poisoning cases including the cause, initial treatments, characteristic of the clinical sign, the laboratory assessment, advanced treatments, healing or recovery, and death. The results were descriptively analyzed by examining the raw data. The data were calculated as the percentage of the groups towards the total subjects. The results showed that the pestiside poisoning management in the Hospital A was adequately performed. The number of the patients that was recovered from poisoning was 34 patients (100%). However, from the viewpoints of initial treatment, laboratory assessment, and poisoning therapy, the poisoning management still needs to be improved.